2013
DOI: 10.1002/2013ja018975
|View full text |Cite
|
Sign up to set email alerts
|

Nonmigrating diurnal tides observed in global thermospheric winds

Abstract: Nonmigrating diurnal tides between 90 and 270 km are inferred from Upper Atmosphere Research Satellite (UARS) wind imaging interferometer (WINDII) winds. This study represents the first known effort to directly analyze tidal wave number structure and propagation direction in winds observed over this altitude range. Prominent diurnal tides include an eastward propagating wave number 3, a zonally symmetric tide, and a westward propagating wave number 2. UARS High Resolution Doppler Imager winds between 60 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 51 publications
6
42
0
Order By: Relevance
“…In addition, Jones et al (2013) demonstrate that the longitudinally varying ionosphere can, through ion drag interactions involving the DW1 (migrating or Sun-synchronous) wind field excited in situ in the thermosphere, produce significant D0 and DW2 tidal components during nonsolar-minimum conditions. The in situ generation of these waves was in fact suggested by Oberheide et al (2011b) based on CHAMP accelerometer measurements, and observational evidence for an in situ driven D0 is provided by Lieberman et al (2013). Jones et al (2013) have shown that additional diurnal and semidiurnal tidal components are generated with this mechanism and with greater efficiency for higher levels of solar activity.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, Jones et al (2013) demonstrate that the longitudinally varying ionosphere can, through ion drag interactions involving the DW1 (migrating or Sun-synchronous) wind field excited in situ in the thermosphere, produce significant D0 and DW2 tidal components during nonsolar-minimum conditions. The in situ generation of these waves was in fact suggested by Oberheide et al (2011b) based on CHAMP accelerometer measurements, and observational evidence for an in situ driven D0 is provided by Lieberman et al (2013). Jones et al (2013) have shown that additional diurnal and semidiurnal tidal components are generated with this mechanism and with greater efficiency for higher levels of solar activity.…”
Section: Introductionmentioning
confidence: 92%
“…This leads to tidal amplitudes in the MLT that can be on the order of the background mean flow, and the overall dynamics of the MLT are thus considerably impacted by solar driven atmospheric tides. Furthermore, during solar minimum conditions when tidal dissipation is weak, the DE3 can propagate into the upper thermosphere, introducing longitudinal variability into thermospheric density and neutral winds Häusler and Lühr, 2009;Liu et al, 2009;Oberheide et al, 2009;Lieberman et al, 2013]. In particular, the eastward propagating nonmigrating diurnal tide with zonal wave number 3 (DE3) is recognized as having a significant influence on generating a wave number 4 longitudinal structure in the ionosphere and thermosphere, when viewed from a fixed local time perspective [e.g., England, 2012, and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in recent studies, the longitudinal variations of Sq have their origin at least partly from an influence of non-migrating tides (e.g., Lieberman et al 2013). Further, the ionospheric gyrofrequencies are proportional to the background magnetic field B, so the ionospheric conductivities decrease with increasing B (e.g., Richmond 1995, Stening andWinch 2013).…”
Section: Sq Foci Tracks For Dataset 2 (2011)mentioning
confidence: 79%